Thioredoxin-Interacting Protein (TXNIP) Knockdown Protects against Sepsis-Induced Brain Injury and Cognitive Decline in Mice by Suppressing Oxidative Stress and Neuroinflammation. (5th May 2022) - Zhang, Yu; Xing, Cheng-Jun; Liu, Xiao; Li, Ya-Hong; Jia, Jing; Feng, Jian-Guo; Yang, Cheng-Jie; Chen, Ye; Zhou, Jun
Abstract : Sepsis-associated encephalopathy (SAE) is linked to increased morbidity and mortality rates in patients with sepsis. Increased cytokine production and neuronal apoptosis are implicated in the pathogenesis of the SAE. Neuroinflammation plays a major role in sepsis-induced brain injury. Thioredoxin-interacting protein (TXNIP), an inhibitor of thioredoxin, is associated with oxidative stress and inflammation. However, whether the TXNIP is involved in the sepsis-induced brain injury and the underlying mechanism is yet to be elucidated. Therefore, the present study was aimed at elucidating the effects of TXNIP knockdown on sepsis-induced brain injury and cognitive decline in mice. Lipopolysaccharide (LPS) was injected intraperitoneally to induce sepsis brain injury in mice. The virus-carrying control or TXNIP shRNA was injected into the lateral ventricle of the brain 4 weeks before the LPS treatment. The histological changes in the hippocampal tissues, encephaledema, and cognitive function were detected, respectively. Also, the 7-day survival rate was recorded. Furthermore, the alterations in microglial activity, oxidative response, proinflammatory factors, apoptosis, protein levels (TXNIP and NLRP3 inflammasome), and apoptosis were examined in the hippocampal tissues. The results demonstrated that the TXNIP and NLRP3 inflammasome expression levels were increased at 6, 12, and 24 h post-LPS injection. TXNIP knockdown dramatically ameliorated the 7-day survival rate, cognitive decline, brain damage, neuronal apoptosis, and the brain water content, inhibited the activation of microglia, downregulated the NLRP3/caspase-1 signaling pathway, and reduced the oxidative stress and the neuroinflammatory cytokine levels at 24 h post-LPS injection. These results suggested a crucial effect of TXNIP knockdown on the mechanism of brain injury and cognitive decline in sepsis mice via suppressing oxidative stress and neuroinflammation. Thus, TXNIP might be a potential therapeutic target for SAE patients.